Anatomy and Cytogenetic Identification of a Wheat-Psathyrostachys huashanica Keng Line with Early Maturation. - Liangming Wang; Yang Liu; Wanli Du; Fan Jing; Zhonghua Wang; Jun Wu; Xinhong Chen (PLoS ONE, 2015)
In previous studies, our research team successfully transferred the Ns genome from Psathyrostachys huashanica Keng into Triticum aestivum (common wheat cv. 7182) using embryo culture. In the present study, one of these lines, i.e., hybrid progeny 25-10-3, which matured about 10-14 days earlier than its wheat parent, was assessed using sequenced characterized amplified region (SCAR) analysis, EST-SSR and EST-STS molecular markers, and genomic in situ hybridization (GISH). We found that this was a stable wheat-P. huashanica disomic addition line (2n = 44 = 22 II) and the results demonstrated that it was a 6Ns disomic chromosome addition line, but it exhibited many different features compared with previously characterized lines, i.e., a longer awn, early maturation, and no twin spikelets. It was considered to be an early-maturing variety based on the early stage of inflorescence initiation in field experiments and binocular microscope observations over three consecutive years. This characteristic was distinct, especially from the single ridge stage and double ridge stage until the glume stage. In addition, it had a higher photosynthesis rate and economic values than common wheat cv. 7182, i.e., more spikelets per spike, more florets per spikelet, more kernels per spike, and a higher thousand-grain weight. These results suggest that this material may comprise a genetic pool of beneficial genes or chromosome segments, which are suitable for introgression to improve the quality of common wheat.